The therapeutic encounter : a cross-modality approach - Bott, David; Howard, Pam (SAGE, 2012)
Focusing on the client-therapist relationship at the core of counselling & psychotherapy practice, this book introduces a model effective across all therapeutic approaches. It provides a cross-modality framework for practice by engaging the trainee directly in the drama of the therapeutic encounter